P4.090 Reminders Remain the Best Client Driven Adherence Coping Strategy For Those Taking Lifelong on Anti Retro Viral Therapy (ART)-The AIDS Support Organization (TASO) Operational Research Findings. (13th July 2013) - Kawuba, A; Denis, M; Nathan, K; Faridah, N; Shafik, M
Abstract : Background: For one to register ART success, good adherence is of utmost importance. With Art paradigm shift clients face a number of challenges in the long term that requires long term strategies for success. A study to assess the major ART adherence coping strategies among clients enrolled on treatment with a four years and above experience was conducted. Method: This was a cross sectional study by design using semi structured questionnaires. Data was analysed using logistic regression model. Convenient sampling targeting a total of 400 TASO clients aged 18 years and above, with over four years experience on ART first line Regimen. Results: A total of 400 clients were interviewed and 43% coped by using reminders, 0.3% by their times of brushing their teeth, 7.5% by before and after morning and evening prayers, 1% by counsellors support, 9.5% by their medicine companions and 38.8% had this as a habit. Conclusion: Majority of the clients use reminders for good adherence in the long term. Baseline adherence preparation is very important since it directly leads to development of positive adherence habits.